A Need-Based Study of Bloom’s Taxonomy in Modern ESL Teaching for Adolescent Learners in the AI Era - Vattaparambil , Muhammed Sadique Ali (The Lingua Spectrum, 2025)
In the current landscape of global education, the integration of artificial intelligence (AI) in language instruction demands a re-evaluation of traditional pedagogical frameworks. This study investigates the relevance and adaptation of Bloom’s Taxonomy within modern English as a Second Language (ESL) classrooms, particularly for adolescent learners in the AI-driven era. Through a needs-based analysis, the research explores how cognitive learning objectives align with contemporary teaching practices, learner preferences, and AI-enhanced tools. The findings highlight the necessity to recalibrate Bloom’s hierarchical model to suit the cognitive, emotional, and technological needs of adolescent ESL learners, advocating for a hybrid model that supports both critical thinking and AI-mediated learning.